Study the effect of Peganum harmala L. Alkaloids Extract in-vivo as Anti-Inflammatory Agent - Ramadhan, Usama H. (University of Thi-Qar Journal of Science, 2013)
The Peganum harmala (L.) have some activities, the alkaloids are from indole series expected have antiinflammatory activity. The alkaloids were extracted by two methods first by ethanol, the second by acidify water with acetic acid. The extracts were tested for anti-inflammatory test by carrageenan induced inflammation test on mice, and the percentage of inflammation inhibition was calculated. The drug (diclofenac sodium) was used as standard drug. The alkaloids extracted by acidify method shows significant activity (p < 0.01) at 2 and 3 hours. The percentages of inhibition were approximated to that were estimated of diclofenac sodium drug. The results indicated the alkaloids that were extracted as salts according to second method were more potent towards inflammation redaction